Study of psychological features of communication in modern family and their impact on personal growth of preschooler - Kateryna Lysenko-Helembiuk; Mariana Shupiana (Vasyl Stefanyk Precarpathian National University, 2017)
The article studies the impact of communication system in family on the formation of personality, psychological characteristics of communication in modern family in the context of foreign and home science are defined, communication and behavior styles in interpersonal interactions of a family are demonstrated, their impact on the formation of personal identity is analyzed, and also the author's psychological-pedagogical model of communicative transformation in family in the personal development of preschooler is justified. Key words: communication, transformation of communication, preschool age, development, sensitive period, incipience of personality, style of communication, "I-message".